UNSUR-UNSUR BEHAVIORISME DALAM KEBIJAKAN WAKIL KEPALA MADRASAH BIDANG KURIKULUM MADRASAH TSANAWIYAH - Kholis, R. Ahmad Nur (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2017)
This study aims to: (1) describe the elements of forming of new behaviors that are expected (shaping) in the policy of the Deputy Head of Student Affairs of MTs Nahdlatul Ulama; (2) describe the elements of the unexpected loss of bad behavior in the policy of the Deputy Head of Madrasah in the Student Affairs of MTs Nahdlataul Ulama; (3) describe the elements of giving reinforcement to students' behavior that are in line with expectations in the policy of the Deputy Head of Student Affairs of MTs Nahdlatul Ulama. This type of research is research kualitataif that uses a case study approach. Data mining is done by means of interviews and observations. The results showed that: (1) the elements of the formation of student behavior (Shaping) in the policy field of Student Deputy Chief of MTs Nahdlatul Ulama is seen in the following matters: (a) the enforcement Hiatus Worshipers; (b) the existence of a code of conduct book used to record violations of Learners; (c) Actuating carried out student representatives; (d) delay in Registration of students in book order; (d) examination of learners who have not attended after the arrival of teachers in every classroom. (2) the elements of the unexpected behavior of the disappearance (Extinction) in policy Deputy Head of Student Field MTs Nahdlataul is as follows: (a) the granting of a culture that is relatively new compared to what there is in the House learners; (b) the awarding of the penalty for those who violate the rules set; and (c) in the process of the penalty of the learners are given a warning to give knowledge of the nilal religious and cultural values is good (3) grant of reinforcement elements (Reinforcemen) Deputy Head of the Madrasa in the policy field of Studentship in MTs Nahdlatul Ulama is seen in the following matters: (a) the giving of reward for good achievers Learners for academic or non academic; and (b) the gift-giving can be shaped or non meteri materials showing the achievements of Learners in a news bulletin or the school wall magazines.